From epidemic to pandemic: Did the COVID-19 outbreak affect high school program choices in Sweden? - Aino-Maija Aalto; Dagmar Müller; J. Lucas Tilley (Research Institute of Industrial Economics (IFN), 2021)
Ceding ownership to outside investors provides a control dilemma for founders. In less developed capital markets with weaker formal institutions, we argue that retained founder director ownership can lower the transaction costs of external capital. Our argument rests on incomplete contracting and institutional theory, particularly highlighting the elevated status of the founding entrepreneur. Based on a longitudinal study of 179 listed Caribbean firms, we find that retained founder ownership reduces information asymmetry vis-à-vis outside minority investors. The reduced information asymmetry is even stronger for firms with a related party/subsidiary within a tax haven, and for firms with strong shareholder rights.
Keywords: I20; J24; 330; COVID-19; business cycle; human capital investment; field of study